Locke, Active Power, and a Puzzle about Ascription - Wood, Joshua M. (Locke Studies, 2023)
Locke traces the concept of active power to the experience of voluntary action in ourselves. I argue that Locke does not find in voluntary action a necessary connection binding volition and action. I defend the application of Locke’s regularity theory of causal judgment to the operation of the will. The will is classified as a cause because it is regularly accompanied by a movement in our limbs or a change in our thoughts. I argue that Locke does not equate the concepts of cause and active power. He maintains that something can serve as a cause, and so bring about change, in virtue of activity or in virtue of its susceptibility to external influence. I go on to develop what I refer to as the ascription puzzle. Locke, who provides a criterion for classifying something as a cause, does not develop a criterion of for classifying causes as either active or passive in nature. The ascription puzzle is vexing because Locke has no principled way to establish, among other things, that humans, in acting voluntarily, exercise active power. The result is that Locke should not be taken to identify the experience of voluntary action as the origin of the concept of active power because of any metaphysical considerations bearing on human agency.